The impact of indoor air quality and contaminants on respiratory health of older people living in long-term care residences in Porto - Mendes, Ana (2016)
Funding This work was supported by GERIA Project PTDC/ SAU-SAP/116563/2010, a PhD Grant (SFRH/BD/72399/ 2010) from Foundation for Science and Technology (Fundação para a Ciência e Tecnologia - FCT) through Operational Competitiveness Programme (COMPETE) as part of the National Strategic Reference Framework and a grant funded by AIRC (Associazione Italiana per la Ricerca sul Cancro).